Diseño curricular de proyectos formativos para el desarrollo de la educación por competencias: Curriculum Design of Training Projects for the Development of Education by Skills - Rodelo Molina, Milys Karina; Acevedo Correa, Diofanor; Montero Castillo, Piedad Margarita (Universidad del Zulia, 2021)
The research has the purpose of characterizing the teaching practice from the curricular design of training projects with the purpose of achieving education by competencies. In this sense, we use the case study in a Mundo Bolivariano District Educational Institution. Focus groups are made up of directors, teachers, students and experts in the curriculum that make up the educational unit. Next, we use data analysis through documents, interviews and bibliographic research in order to collect relevant information. We identify that the curriculum excludes the full identification of situations and context characteristics. Also, teachers lack the proper training to organize and carry out competency education. The inquiry approach used is a Participatory-Action-Research type.